Prevención del acoso escolar mediante la gestión en resolución de conflictos para los estudiantes de básica superior en la Unidad Educativa “Adolfo Valarezo” 2023 2024. - Rodriguez Mora, Gabriela Cristina (2024)
This Curricular Integration paper entitled “Prevention of school harassment through conflict resolution management for high school students in the Unidad Educativa "Adolfo Valarezo" 2023 2024, has the following general objective: To analyse the prevention of school harassment through the management and resolution of conflicts in high school students of the Unidad Educativa "Adolfo Valarezo" 2023 2024. It is an investigation of a qualitative approach and a descriptive non- experimental and cross-sectional nature, that uses methods such as: inductive, analytical-synthetic and scientific, in order to address the subject of study. The techniques that were used include in- depth interviews to 8 teachers, as well as direct observations that were made to the students inside the classroom, which provided detailed data of the subject of the investigation. The results evidenced significant variations in teachers' abilities to manage and resolve conflicts related to school harassment. Some teachers demonstrated remarkable skills in mediation and conflict management, while others faced difficulties in identifying and resolving these problems effectively. Also, it was observed that most students experienced conflict situations that affected their emotional well-being and academic performance. The research concludes that it is necessary to design an educational intervention proposal that includes a guide of activities to strengthen teachers' conflict management and resolution skills, thus providing effective tools to address the deficiencies observed. This intervention will not only improve academic performance and the school environment, but will also foster a safe and respectful educational environment, consequently promoting peaceful coexistence and emotional well-being for all members of the educational community.